A study of culture-specific items in Jean M. James’s translation of Luotuo Xiangzi: an analysis of translation strategies and challenges based on Aixelá’s Theory - Xiaohan Guo,; Mohamed Abdou Moindjie,; Paramaswari Jaganathan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Culture-specific items have been central in translation studies. Aixelá (1996) defines and classifies them and proposes translation strategies that advance research. Luotuo Xiangzi, which has been translated into four English editions, is a landmark in modern Chinese literature and has attracted worldwide interest. Among these, the translation by Jean M. James stands out for its recognition and inclusion in prominent American university libraries. Despite this, research on James’s translation remains limited, particularly regarding her handling of culture-specific items. To address this gap, the present study, guided by Aixelá’s theoretical framework, conducts a comprehensive analysis of James’s culture-specific items translation strategies and the challenges she faced in translating culturally bound expressions from Chinese into English. Utilizing a qualitative methodology, the study identifies key factors influencing James’s translation decisions and explains major challenges in dealing with Chinese culture-specific items. The findings reveal Jean M. James’s preference for conservative-oriented strategies over substitution-oriented strategies, such as linguistic translation, orthographic adaptation, and intratextual glosses, reflecting her tendency to preserve cultural nuances rather than replace them with target culture equivalents. This translation foreignization-oriented strategy preserves the cultural context of the source language and increases readers' understanding of the source language's culture. This study provides new insights into the practical application of Aixelá’s theory in Chinese-English literary translation and highlights the complexities of cross-cultural translation practices.